(untitled) (Economics and region, 2025)
The article describes the retrospective development of the concept of «information» and transformational changes in understanding its meaning in scientific discourse. The role of information in ensuring the functioning of economic systems is identified, which consists in its use as a resource for enterprise management, a strategic basis for an innovative economy, a factor in marketing and competitiveness, and a resource element for enterprise development. It has been established that in the current economic conditions, information is a basic resource for enterprises, ensuring the effective management of other types of production resources. The role of information in the economic activity of enterprises is specified, in particular as a strategic intangible resource that covers a certain amount of data useful for enterprise management about its internal processes and external environment, which, in conditions of increased risks of activity, ensure effective management decisions, the formation of competitive advantages, and the stability of the enterprise. The concept of asymmetric information theory has been adapted to the functioning of domestic markets. It has been determined that information asymmetry in Ukrainian markets is exacerbated by military actions, in particular by provoking a high level of uncertainty in business activities, entrepreneurial risk, increasing information gaps between partners, and distorting the information environment through intensive disinformation and propaganda. The priority of timeliness of information in determining the value of economic information as opposed to technical information has been established. The essence of the concept of «information security» has been identified and it has been established that it can be applied to the state, society, individual citizens, and enterprises. It has been determined that the information security of an enterprise strongly correlates with its economic security, since any management decisions in the economic activities of enterprises are based on information; their qualitative characteristics and effectiveness will directly depend on the quality of the information on the basis of which they were previously adopted.